Simulador PhET para el aprendizaje de Física, unidad dos: Ondas en los estudiantes de tercero año de Bachillerato General Unificado. - Rivera Gutiérrez, Sofía Isabel (2024)
It is crucial that educators acquire new technologies and use teaching methods in order to create a more dynamic and effective learning environment that meets the needs of today's students and prepares them for the challenges of the future. Therefore, this work aims to relate the learning of Physics with the PhET simulator in unit two: Waves in third-year students of the unified general high school. To carry out the research, a qualitative, documentary-type approach with a non-experimental and exploratory-descriptive design was used. The method used was the bibliographic review and the search log with content sheets was applied to collect information. The result was that using the PhET simulation strengthens physics learning, since it allows the teacher to provide teaching to their students and provide content in an interactive way, promoting attention, participation and motivation. Keywords: Physical, education software, technological resource, learning.